The - Robinson, Chris (AWN Press, 2007)
For five years, Chris Robinson wrote a monthly column for Animation World Network (AWN) called The Animation Pimp. Although it began as a way for Robinson to let off steam in his role as director of one of the world's largest animation festivals, the column quickly gained a cult following and just as quickly became a platform for the author's frank, provocative, and frequently very funny musings on the world of animation and his own life. The Animation Pimp collects the best of these pieces, which range from the nuts and bolts of running a festival to sex, death, superheroes, aesthetics, and the living dead. Robinson's unhinged prose is accompanied by some eighty drawings by the award-winning German artist and animator Andreas Hykade. In the spirit of Hunter Thompson, Nick Tosches, and Richard Meltzer, The Animation Pimp is an outrageous, funny, and ultimately truthful account of the chaos and glimmers of illumination in an art form and a life. The Animation Pimp is the first in a series of official guides published in collaboration with AWN Press. Each book covers major facets of the animation industry and offers a one-of-a-kind look into the careers of industry icons